Using Language Learning Software to Learn Vocabulary: Tell Me More Through the Lenses of Engineering Students - Zuraina, Ali (Necmettin Erbakan University, 2019)
This study examines the uses of Tell Me More (TMM) software among engineering students in Universiti Malaysia Pahang (UMP). The study aims at finding students’ abilities in retaining words learnt through Pre-test and Delayed Recall Post-test. The study also aims at identifying their preferences and challenges in using TMM. The study employed 43 students that were required to take vocabulary tests and participated in interviews to gauge their perceptions of using TMM. Results showed that there was a significant increase in the tests administered. The qualitative findings showed that students preferred the drag-and-drop feature in the software; among others. Yet, there were challenges in imitating the native-speaker in pronouncing target words, accessing TMM outside class hours and linking target words with its meaning. These findings provide empirical data for the use of computers in learning vocabulary.